2011
DOI: 10.1093/jxb/err328
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the maize ZmGF14-6 gene in rice confers tolerance to drought stress while enhancing susceptibility to pathogen infection

Abstract: 14-3-3 proteins are found in all eukaryotes where they act as regulators of diverse signalling pathways associated with a wide range of biological processes. In this study the functional characterization of the ZmGF14-6 gene encoding a maize 14-3-3 protein is reported. Gene expression analyses indicated that ZmGF14-6 is up-regulated by fungal infection and salt treatment in maize plants, whereas its expression is down-regulated by drought stress. It is reported that rice plants constitutively expressing ZmGF14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 61 publications
(87 reference statements)
3
40
0
1
Order By: Relevance
“…Regarding the implication of 14-3-3 proteins in mediating stress signaling, a number of studies have demonstrated that they have an important function in plant responses to biotic stresses (Gökirmak et al, 2010). However, although the expression of 14-3-3 genes is induced by several abiotic stresses, including cold (Jarillo et al, 1994), high salt (Xu and Shi, 2006), and drought (Porcel et al, 2006), as well as phosphorous and iron deficiencies (Wang et al, 2002;Cao et al, 2007), evidence for 14-3-3-mediated abiotic stress responses is still very limited (Yan et al, 2004;Campo et al, 2012;Yang et al, 2013;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the implication of 14-3-3 proteins in mediating stress signaling, a number of studies have demonstrated that they have an important function in plant responses to biotic stresses (Gökirmak et al, 2010). However, although the expression of 14-3-3 genes is induced by several abiotic stresses, including cold (Jarillo et al, 1994), high salt (Xu and Shi, 2006), and drought (Porcel et al, 2006), as well as phosphorous and iron deficiencies (Wang et al, 2002;Cao et al, 2007), evidence for 14-3-3-mediated abiotic stress responses is still very limited (Yan et al, 2004;Campo et al, 2012;Yang et al, 2013;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The gene-specific expression patterns in response to diverse environmental stimuli imply that the isoform specificity exists in the 14-3-3 gene family in plants (Xu et al 2012;Sun et al 2014;Xu and Shi 2006;Roberts et al 2002;Denison et al 2011). Several studies have provided genetic evidences to show that individual 14-3-3 isoforms have specific functions during plant development (Radwan et al 2012;Mayfield et al 2012;Li et al 2012;Moriuchi et al 2004) and in adaptation to diverse environmental conditions (Xu et al 2012;Sun et al 2014;Yan et al 2004;Manosava et al 2011;Xu et al 2013;Campo et al 2012). Most of the higher plants have more than one PM H ?…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection and salt treatment were found to result in up-regulation of ZmGF14-6 in maize plants, whereas drought stress caused down-regulation of this gene. When rice plants with constitutive expression of ZmGF14-6 were generated, they showed increased drought tolerance (Campo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OsGF14e has been implicated to have a role in disease resistance through negative effects on the induction of plant defense response genes and cell death (Manosalva et al 2011). Although the gene expression of 14-3-3 proteins under various environmental stress has been investigated (Chen et al 2006;Xu and Shi 2006;Manosalva et al 2011;Campo et al 2012;Xu et al 2012a), expression profiling of the rice 14-3-3 gene family in response to As stress has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%